Perilaku Masyarakat (Antropocentrisme) dalam Membuang Sampah di Jalan Anggrek Kereng Bangkirai Kota Palangka Raya - Muhammad Azhari; Kamaliah Kamaliah; Rudy Yoga Lesmana (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Garbage is a problem for the environment. People who lack knowledge about waste processing and management cause problems for the environment, for example on Jalan Anggrek Kereng Bangkirai, City of Palangka Raya The research was carried out using observation techniques from 2015 to 2021. The results obtained were infrastructure that was not yet available in the field of waste sanitation, lack of knowledge about waste, and supervision from security and cleanliness so that people freely dispose of garbage on the road and waste processing is still limited. The perpetrators of garbage disposal are more dominant in the community who live outside the Jalan Anggrek.